Escolarização de crianças com fissura lábio palatina - Silva, Glorismar Gomes da (2018)
The Cleft Lip and Palate (CLP) are congenital malformations affecting the facial region, whose cleft or opening communicates the oral and nasal regions, causing air leak through the nose and hypernasalized voice. It is frequent in our population and the prevalence of one child per 650 births. The schooling of children is not well-explored scientifically and educational demands of these students have remained on the sidelines of the debate about inclusive education. Studies and research on CLP treat predominantly clinical, functional and malformat on rehabilitation aspects. This study questions: Do the sequels generated by the orofacial malformations, the long surgical and rehabilitation process by which a person with CLP goes through, impact directly their social relations, the development of the child and, consequently, their schooling process? This study aims at identifying the educational needs of the child with CLP in the schooling period that includes the early childhood education and the early years of elementary school and characterize the school experience of these children. To this end, three studies were carried out. Study 1- academic production on the child's schooling with CLP bibliographic survey to identify school-related aspects of people with CLP. Study 2 - sample characterization of children with CLP in age of initial schooling: survey using the medical records of the HRAC-USP. Study 3 - Children with CLP in school: their voices and the speeches of mothers and of teachers: children with CLP, their mothers and teacher were interviewed about the child´s school life. The results of the three studies indicated a shortage in academic production of studies on schooling of children with CLP in the school context. In relation to the sample of 300 medical records of the children, in the age group from 4 to 16 years of age, the research found out that the majority of the were male (61,3%), went through 3 to 4 surgeries, were white (98%), missing data on age/schooling gap. In the third study, the interview analysis revealed the participants' lack of knowledge about CLP; the satisfaction of mothers with the schooling and sociability of their children; at the same time, the difficulties of mothers and teachers to recognize the impact of FLP's consequences on communication and behavior of children, as well as the consequences for schooling, were identified. According to the results of the three studies, it can be inferred that there is still a lack of knowledge about schooling of children with CLP and its implications for school life, as well as limits of research in the educational literature on this population. With the present study, it was intended to bring the theme to the scope of the National Policy of Special Education and to the context of the schools. It is necessary, therefore, to expand the research in the area that contemplate this population, in order to fulfil the social role of the school to meet the diversity of students with a quality education and focused to meet the educational needs of all.